The Interconnection between Mathematics and Muhammadiyah Islamic Teachings - Syah, Arga; Fathurohman, Oman (The Indonesian Institute of Science and Technology Research, 2025)
This article explores the intersection of mathematics and Islamic values, emphasizing their roles in education and cultural development. The primary goal is to elucidate how mathematics serves not only as a tool for intellectual development but also as a means to instill character and ethical values in learners. The study addresses the problem of integrating abstract mathematical concepts with moral teachings rooted in Islamic principles, aiming to enhance students' cognitive, affective, and psychomotor skills while fostering virtues like honesty and diligence. Methodologically, the article reviews literature on mathematical characteristics and their application in Islamic civilization, particularly in science and technology. It also examines Quranic perspectives on mathematics and the universe, highlighting how mathematical principles reflect the eternal attributes of Allah. The analysis draws on historical and theological insights to demonstrate how mathematics can inspire spiritual growth and appreciation for divine creation. Results indicate that mathematics, when integrated with Islamic teachings, promotes ethical behavior and enhances students' understanding of the universe's order and beauty. This study contributes to the broader discourse on educational strategies that integrate faith-based values with academic disciplines, promoting a balanced worldview and ethical consciousness among learners. In conclusion, the synthesis of mathematics and Islamic values offers a comprehensive framework for character development and intellectual growth, underscoring the importance of interdisciplinary approaches in contemporary education.